An Ayurvedic Management of BPH by Uttar Basti Therapy (UBT) - Anu Kotiya; Lakshman Singh; AK Dwivedi (AYUSHDHARA, 2023)
Benign Prostatic Hyperplasia is the most common disease condition found in aged men that causes difficulty in micturition, urgency, intermittency and weak stream. The symptoms of BPH are coherent with Vatashtheela: one of the 12 types of Mutraghata, which is clearly defined by Acharya Sushrut as difficulty in micturition due to growth near bladder neck. A single case study of a 43-year-old man having complaint of increased frequency of micturition, nocturia and straining diagnosed with BPH is being presented here. After taking detailed history and thorough examination UBT was planned for this patient with Shilodbhidadi taila which produced admirable symptomatic and clinical results and fulfils the critical need of a therapeutic modality as BPH lowers patients' quality of life (QoL) and places a significant socioeconomic burden on the healthcare system.